Nerve biopsy in acquired neuropathies. (14th September 2021) - Sommer, Claudia; Carroll, Antonia S; Koike, Haruki; Katsuno, Masahisa; Ort, Nora; Sobue, Gen; Vucic, Steve; Spies, Judith M; Doppler, Kathrin; Kiernan, Matthew C
Abstract: A diagnosis of neuropathy can typically be determined through clinical assessment and focused investigation. With technological advances, including significant progress in genomics, the role of nerve biopsy has receded over recent years. However, making a specific and, in some cases, tissue‐based diagnosis is essential across a wide array of potentially treatable acquired peripheral neuropathies. When laboratory investigations do not suggest a definitive diagnosis, nerve biopsy remains the final step to ascertain the etiology of the disease. The present review highlights the utility of nerve biopsy in confirming a diagnosis, while further illustrating the importance of a tissue‐based diagnosis in relation to treatment strategies, particularly when linked to long‐term immunosuppressive therapies,